函数f(x)=2cosx(sinx-cosx)+1 化简.详细步骤:f(x)=2cosxsinx-2cosxcosx+1 =sin2x-cos2x =√2*sin(2x-π/4)请问:=√2*sin(2x-π/4) 怎么推到出来的呢?

来源:学生作业帮助网 编辑:作业帮 时间:2024/05/09 12:09:36
函数f(x)=2cosx(sinx-cosx)+1 化简.详细步骤:f(x)=2cosxsinx-2cosxcosx+1     =sin2x-cos2x     =√2*sin(2x-π/4)请问:=√2*sin(2x-π/4) 怎么推到出来的呢?
x){ھ iFřy Ӟi5Xgk\Y``5-PlQDQ,#-P|_N_4 SJYCߓV<}׳Kjy:qMR>Ykh4ˑD1#v6C/) ho QbUTrT13^"6j'5c U<PFbvR_,쁄~qAb4l';vXl+OY =/Ozv3Ytgv>|m]}@/}qCo

函数f(x)=2cosx(sinx-cosx)+1 化简.详细步骤:f(x)=2cosxsinx-2cosxcosx+1 =sin2x-cos2x =√2*sin(2x-π/4)请问:=√2*sin(2x-π/4) 怎么推到出来的呢?
函数f(x)=2cosx(sinx-cosx)+1 化简.详细步骤:
f(x)=2cosxsinx-2cosxcosx+1
=sin2x-cos2x
=√2*sin(2x-π/4)
请问:=√2*sin(2x-π/4) 怎么推到出来的呢?

函数f(x)=2cosx(sinx-cosx)+1 化简.详细步骤:f(x)=2cosxsinx-2cosxcosx+1 =sin2x-cos2x =√2*sin(2x-π/4)请问:=√2*sin(2x-π/4) 怎么推到出来的呢?
f(x)=2cosxsinx-2cosxcosx+1
=sin2x-cos2x
=√2[sin2x *(√2/2)-cos2x*(√2/2)]
=√2[sin2x*cosπ/4-cos2x*cosπ/4]
=√2*sin(2x-π/4)
asinα+bcosβ或asinα-bcosβ
提取√(a^2+b^2)进行化简!

主要是利用的同角正余弦平方和等于1的知识。